Synthetic and Catalytic Potential of Amorphous Mesoporous Aluminosilicates Prepared by Postsynthetic Aluminations of Silica in Aqueous Media. Issue 6 (14th February 2018) - Locus, Roel; Verboekend, Danny; d'Halluin, Martin; Dusselier, Michiel; Liao, Yuhe; Nuttens, Nicolas; Jaumann, Tony; Oswald, Steffen; Mafra, Luís; Giebeler, Lars; Sels, Bert
Abstract: Amorphous aluminosilicate catalysts have been used industrially on a large scale for almost a century. However, the influence of the pH on the alumination of silica in aqueous solutions has remained largely unclear. Herein, room temperature aluminations of different mesoporous amorphous silicas (fumed silica, dried silica gel, SBA‐15, MCM‐41, and COK‐12) with aqueous solutions of various pH (3–13) are explored. The aqueous solutions are prepared using different aluminum sources (Al(NO3 )3 or NaAlO2 ) and alkaline additives (NaOH or NH4 OH). The decoupling of pH and Al source using alkaline additives results in a vast experimental potential to prepare unique aluminosilicates, whereby an important role is played by the pH development during the treatment. The bulk and surface composition, acidity, aluminum coordination, morphology, hydrothermal stability, and porosity of the obtained materials are characterized. Optimal samples possess large surface areas and superior acidities (up to 50 % higher) and outstanding stabilities compared to aluminosilicates prepared with state‐of‐the‐art methods. The obtained materials are evaluated in a series of acid‐catalyzed model reactions involving substrates of various chemical reactivity and size, enabling insight in the catalytic functionality of the introduced Brønsted and Lewis sites. The potential of the obtained materials is emphasized by the similar or superior acidity and catalytic performance compared to several benchmark industrial silica–alumina‐based catalysts. Abstract : All comes down to the acidity : Controlling the pH of Al‐containing aqueous solutions yields porous aluminosilicates with superior acidity and stability. The effectivity of the method is demonstrated on several silica sources. Catalytic evaluation in five distinct acid‐catalyzed reactions underline the potential of the developed materials.